Research into methods and algorithms for generating (pseudo) random sequences over an arbitrary alphabet - Gorbenko, I.D.; Alekseychuk, A.N.; Kachko, Ye.G.; Derevianko, Ya.A. (Radiotekhnika, 2024)
Randomness is an integral component of most special software and hardware CIP tools. Work and development towards improving the process of randomness generation is actively underway and requires special attention. This paper is devoted to the research into algorithms for generating (pseudo)random sequences over an arbitrary alphabet, estimating their complexity (time and capacity), as well as statistical characteristics. This study is important because modern post-quantum algorithms use such sequences to generate keys and random components of digital signatures and key encapsulation. Obtained results can serve as a motivation for choosing an algorithm for generating sequences of an arbitrary alphabet for use in certain cryptographic transformations or algorithms.